Artificial Intelligence Adoption Practices in Scholarly Publishing of Early-Stage Academic Researchers - Rosario, Leo Mendel; Gamit, Sean Patrick; Navigar, Noel; Mendoza-Armiendo, Regina; San Pablo, Shari Eunice (Journal of learning theory and methodology (Online), 2025)
Background. Artificial intelligence has drastically changed work environments, resulting in skill shifts in the workforce.  With catch-up formal instructions on AI utilisation, adult learners rely on self-directed and experiential learning for upskilling and reskilling of technology adoption in their workflows. In higher education, students and faculty employ various strategies for adopting AI technology in academic course requirements and research undertakings. Developing a theory of planned behaviour for the adoption of generative AI in an educational setting requires an investigation of perceived and actual behavioural controls of non-users and users of AI applications.  Objectives. This study investigated the AI adoption practices of early-stage academic researchers in a teaching-focused institution for scholarly publishing.  Materials and methods. The intention and behaviour of AI adoption and utilisation were examined for 50 graduate students and 50 academic faculty from a teaching-focused higher education institution. An AI utilisation framework was adapted to investigate the four components of scholarly publishing: research conception, academic writing, editing and proofreading, and academic publishing. Descriptive statistics were used to present and analyse AI adoption and utilisation patterns in scholarly writing and publishing.  Results. Findings show that only half of the respondents used AI for idea extraction, grammar checking, and paraphrasing. Furthermore, there was a general perception of satisfactory ability for the planned and actual utilisation of AI for research conception, academic writing, editing, and proofreading.  Conclusions. As an implication of adult learning theory and methodology, the study provides valuable insights for integrating AI literacy into contemporary educational frameworks.